The Effect of Glibenclamide on the Functional Activity of КATP Channels of Cerebral Arteries in Rats with Streptozotocin Diabetes Mellitus - I. B. Sokolova; G. I. Lobov (Сахарный диабет)
BACKGROUND: In the treatment of diabetes mellitus (DM) for a persistent reduction in blood glucose levels it was widely used glibenclamide — a KATP channels blocker. However, its effects on cerebral circulation have been studied very little. A decrease in the functional activity of KATP channels due to their blocking by glibenclamide against the background of developed endothelial dysfunction may lead to impaired cerebral circulation (especially at the microcirculatory level) and promote remodeling of the vascular network.AIM: To evaluate the effect of glibenclamide on the reactivity of cerebral arteries in rats with streptozotocin-induced diabetes mellitus (STZ-T2DM).TASKS: 1. To study changes in the functional state of KATP channels of pial arteries in STZ-T2DM. 2. To evaluate the effect of glibenclamide on the participation of KATP channels in the formation of basal tone and endothelium-dependent dilatation of pial arteries.MATERIALS AND METHODS: The study was performed on 54 male Sprague Dawley rats. Streptozotocin-induced diabetes mellitus (STZ-T2DM) was modeled by keeping animals on a high-fat diet and administering streptozocin (35 mg/kg). Using an installation for intravital study of pial vessels reactivity, 3 months from the beginning of the experiment, the diameter of the arteries was measured when the brain surface was irrigated with Krebs-Henseleit solution, acetylcholine, glibenclamide, pinacidil and acetylcholine against the background of the action of glibenclamide or pinacidil.RESULTS: With modeling STZ-T2DM, rats developed glucose tolerance and insulin resistance. Compared to control animals, body weight was 1,3 times higher, the percentage of visceral fat was 3 times higher, and the blood glucose level was 3,2 times higher. It was shown that in STZ-T2DM the number of pial artery constrictions under the action of glibenclamide decreased by 1,3 — 1,9 times compared to intact rats. Glibenclamide did not block endothelium-dependent dilation.CONCLUSION: In rats with streptozotocin diabetes, KATP channels take part in the formation of the basal tone of the pial arteries, but the contribution of these channels is reduced on average by 1.5 times compared to healthy rats.The use of glibenclamide in STZ-T2DM does not affect endothelium-dependent dilatation of cerebral arteries.